Association of dietary inflammatory index score with gestational weight gain in 22 to 28 weeks of pregnancy - Riezki Amalia; Rima Irwinda; Okky Lupita Sari (Indonesian Nutrition Association, 2024)
Maternal mental health during pregnancy has a significant impact on early childhood development, but its association with child growth outcomes, notably stunting, has received less attention, particularly in Indonesia.